(untitled) (Bangladesh Journal of Otorhinolaryngology, 2010)
Transsphenoidal approach to sella is not a new approach. In the last 100 years it has gone numerous changing refinements from using headlight to microscope and more recently the sensitive endoscope. In this prospective study, all patients with pituitary tumor who underwent endonasal transsphenoidal pituitary surgery during the period of January 2006 to July 2009 in the department of neurosurgery, Dhaka Medical College Hospital and Islami Bank Central Hospital, Dhaka, Bangladesh were included. Among the 55 patients 36 cases were operated by combined endoscopic and microscopic techniques and 19 cases were operated by endoscope only. Total 73 procedures were done in 55 patients. Age range was 17 years to 70 years. Follow up period was 03 months to 42 months (mean 14.2 months) .Male: female was almost 1:1. Clinical features were pituitary apoplexy, pituitary apoplexy with 3rd/+6th cranial nerve palsy, headache, amenorrhea, loss of libido, galactorrhoea, gynecomastia, weight gain and psychosis. Visual impairment was in 35 cases. Functioning adenoma was 21 and non functioning adenoma was 34 cases. Among the functioning adenoma acromegaly was seen in 12 cases, gigantism in 01 case, prolactinoma in 05 cases, Cushing’s disease 03 cases. Purely sellar tumor was 15, sellar & suprasellar 35 and sellar & parasellar 11 cases. Microscopic plus endoscopic techniques used in 54 procedures. Purely endoscopic procedures were 19. Complete removal of tumor in single stage was done in 33 cases. Complete removal with more than one stage surgery in 13 cases. In our initial cases of the series, we exposed the sella endonasally with endoscope then we used microscope for the rest of the surgery. In the later part of the series we gained experience and confidence for removal of pituitary tumor with an endoscope completely. The rate of diabetes insipidus occurred in 11(20%) cases and all are transient. Postoperative CSF leak was noted in 10(18%) cases. Patient with ocular palsy improved post operatively within 6 weeks. Among non functioning adenoma that were removed completely (30 cases) recurrence occurred in three cases. Eleven patients were stable in vision as preoperative. Other showed visual improvement to variable extents. Key words: Pituitary surgery; Endonasal; Transsphenoidal; Microsurgery; Endoscopic surgery. DOI: 10.3329/bjo.v15i2.5056 Bangladesh J Otorhinolaryngol 2009; 15(2): 45-49